2020
DOI: 10.1140/epjc/s10052-020-7645-z
|View full text |Cite
|
Sign up to set email alerts
|

Holographic p-wave superconductor with $$C^2F^2$$ correction

Abstract: Via numerical and analytical method, we construct the holographic p-wave conductor/superconductor model with C 2 F 2 correction (where C 2 F 2 = C αβ μν C μν αβ F ρσ F ρσ , and C αβ μν and F ρσ denotes the Weyl tensor and gauge field strength, respectively.)in the four-dimensional Schwarzschild-AdS black hole, and mainly study the effects of C 2 F 2 correction parameter denoted by γ on the properties of superconductors. The results show that for all values of the C 2 F 2 parameter, there always exists a critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 61 publications
0
15
1
Order By: Relevance
“…It followed that unlike the case for the six order derivative term C 2 F 2 in Refs. [35,63,64], we observed neither the Drudelike peak near the zero-frequency nor the pronounced peak at the intermediate frequency.…”
Section: Conclusion and Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…It followed that unlike the case for the six order derivative term C 2 F 2 in Refs. [35,63,64], we observed neither the Drudelike peak near the zero-frequency nor the pronounced peak at the intermediate frequency.…”
Section: Conclusion and Discussioncontrasting
confidence: 68%
“…[61], the authors in Refs. [62][63][64] constructed the s-wave and MCV p-wave conductor/superconductor phase transition models via the numerical and analytical methods, respectively, and found that the increasing six derivative correction enhances the superconductor phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…[80,81] In a typical ALD process, the substrate is alternately exposed to different gaseous precursors, which react in a self-limiting manner to deposit metal atoms in an atomic layerby-layer fashion. [91,92] Generally, one complete ALD cycle contains two main processes. [67] Taking the deposition of Pt atoms on graphene as an example (Figure 2), the first step is the reaction between the Pt precursor and the absorbed oxygen on the surface of graphene.…”
Section: Atomic Layer Depositionmentioning
confidence: 99%
“…In this model the vector condensate is induced by a magnetic field, meaning that the emergence of phase transition is induced not only by the chemical potential/charge density, but also by the background magnetic field. Based MCV pwave model, the effects of the Weyl corrections is deeply studied in [36,47]. It is found that the presence of the higher order Weyl corrections facilitates the emergence of the superfluid phase [36].…”
Section: Introductionmentioning
confidence: 99%